PELUANG PENGEMBANGAN WISATA LINTAS BATAS (CROSS-BORDER TOURISM) DALAM MENINGKATKAN PERTUMBUHAN EKONOMI KABUPATEN SAMBAS - Desi Yuniarti (Cross-border, 2021)
The number of tourist visits to Sambas Regency is low but every year it increases to Temajuk Village Tourism. This study aims to analyze the characteristics of tourism actors, tourism potential, tourism development practices, and tourism development factors in Temajuk Village. This case study research collects data from interviews, observations, and focus group discussions (FGD). Informants in the study were selected using a purposive sampling technique based on the characteristics of tourism actors. Testing data through source triangulation, interactive model data analysis using social practice theory from Bourdieu. The results showed that the characteristics of tourism actors consisted of domestic and foreign tourists. tourism service industries such as villas, resorts and homestays, travel agencies "Sambas Destinations", simple food stalls, there is no tourist information center and souvenir center. Tourism services are not optimal because there are no banks/ATMs, poor communication and network services, electricity only flows for 14 hours. There are already sub-sector police and health centers. The government is the Temajuk Village Government and the Regency Government. The majority of the community are Malay, Muslim, and work as farmers and fishermen. The communities are GenPI sambas, Jewita Sambas, and WWF Paloh. The tourism potential of Temajuk Village consists of natural potential including Tanjung Flag Beach, Camar Bulan Beach, mangrove forest, Tropical Rain Forest. Cultural potentials include Jellyfish Dance, Art of Dhikr, and the manufacture of processed shellfish. Other potentials include Jellyfish Season, Seagull Resort, Paloh Coastal Festival, and crab hunting. Development of tourism by increasing attractiveness through improving the quality of marine tourism, implementing the Paloh Coastal Festival, making Mangrove ecotourism. There is an increase in access such as the provision of transportation to Temajuk Village, repair of village roads and bridges. Tourism amenities with the Tourism Awareness Movement and the creation of a souvenir center. Ancillary, namely with Digital Promotion, establishment of BTS, electricity supply, establishment of art studios. Tourism supporting factors consist of natural, social and cultural attractions, events, and tourism supporting facilities as economic capital. The label "a piece of heaven in the tail of Borneo" as a symbolic capital. Cooperation between the community and the actors and the behavior of the giraffe as cultural capital. Inhibiting factors such as the absence of banking facilities, road access, poor internet network and only 14 hours of electricity as economic capital which is an ancillary component and the absence of a Regional Regulation regarding tourism development in Temajuk Village.